Relación entre el crecimiento del crédito al sector privado y el nivel de liquidez del sistema financiero en la región de Loreto durante el periodo 2010–2024 - Ochavano Muñoz, Grecia Aracely (2025)
This research analyzes the relationship between private sector credit growth and the level of financial system liquidity in the Loreto region during the period 2010–2024. The study followed an applied approach with a non-experimental, correlational, and longitudinal design, using quarterly time series data from official sources such as the Central Reserve Bank of Peru, the Superintendency of Banking, Insurance and AFP, and the National Institute of Statistics and Informatics. Through the Spearman correlation coefficient, the general hypothesis was tested, revealing a strong and significant positive relationship (ρ=0.7642; p=0.001), confirming that liquidity is a key determinant of credit expansion in the region. The specific hypotheses also showed consistent associations: between private credit as a percentage of regional GDP and liquidity in local currency (ρ=0.6041), between the total amount of credit granted and the Liquidity Coverage Ratio (ρ=0.5938), and between financial deepening and total liquid assets (ρ=0.5432). The results demonstrate that, although liquidity provides the foundation for credit growth, its impact is conditioned by structural limitations in Loreto, such as low levels of financial inclusion, widespread informality, and limited banking infrastructure. The study concludes that the strength of the regional financial system does not automatically translate into greater credit inclusion, raising challenges for economic policy and financial intermediation in decentralized contexts.